2018
DOI: 10.1021/acs.jmedchem.8b01467
|View full text |Cite
|
Sign up to set email alerts
|

6-Benzhydryl-4-amino-quinolin-2-ones as Potent Cannabinoid Type 1 (CB1) Receptor Inverse Agonists and Chemical Modifications for Peripheral Selectivity

Abstract: A novel series of 6-benzhydryl-4-amino-quinolin-2-ones was discovered as cannabinoid type 1 receptor (CB 1 R) inverse agonists based on the high-throughput screening hit, compound 1a. Structure−activity relationships were studied to improve in vitro/in vivo pharmacology and restrict distribution to the peripheral circulation. We adopted several strategies such as increasing topological polar surface area, incorporating discrete polyethylene glycol side chains, and targeting P-glycoprotein (P-gp) to minimize ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…With a considerably lower exposure in the brain, Compound D4, developed by 7TM Pharma, induced pronounced weight reduction in a dose-dependent manner in obese mice in comparison with rimonabant [146]. Although designed to be a P-glycoprotein (P-gp) substrate in order to decrease its brain penetration, Compound 6a, developed by Janssen Research & Development, accumulated in the brain following chronic administration, suggesting that its in vivo metabolic efficacy cannot exclude blocking central CB 1 Rs [147]. Compound 2p, which originated from the brain-penetrant CB 1 R inverse agonist program of the same group, reduced glucose levels without centrally mediated behavioral effects and a reduction in food intake or body weight [148].…”
Section: Current View Regarding Novel Peripherally Restricted Cb1rmentioning
confidence: 99%
“…With a considerably lower exposure in the brain, Compound D4, developed by 7TM Pharma, induced pronounced weight reduction in a dose-dependent manner in obese mice in comparison with rimonabant [146]. Although designed to be a P-glycoprotein (P-gp) substrate in order to decrease its brain penetration, Compound 6a, developed by Janssen Research & Development, accumulated in the brain following chronic administration, suggesting that its in vivo metabolic efficacy cannot exclude blocking central CB 1 Rs [147]. Compound 2p, which originated from the brain-penetrant CB 1 R inverse agonist program of the same group, reduced glucose levels without centrally mediated behavioral effects and a reduction in food intake or body weight [148].…”
Section: Current View Regarding Novel Peripherally Restricted Cb1rmentioning
confidence: 99%
“…An important factor supporting THCV use in therapy could also be its antipsychotic effect [180]. Other compounds with same pharmacodynamics, i.e., able to influence feeding behaviour, which still require further research include: NESS06SM [181], SM-11 [182], PIMSR [183], BAR-1 [184], Compound10q [185], Compound2c [186], Com-pound5 [172], Compound13 [165], Compound6a [187], and CompoundD4 [188]. These were designed to have low penetration in the brain, except for Compound6a, whose chronic administration caused accumulation in the brain [187].…”
Section: Endocannabinoid System As a Pharmacological Target For Obesity And Food Addictionmentioning
confidence: 99%
“…Other compounds with same pharmacodynamics, i.e., able to influence feeding behaviour, which still require further research include: NESS06SM [181], SM-11 [182], PIMSR [183], BAR-1 [184], Compound10q [185], Compound2c [186], Com-pound5 [172], Compound13 [165], Compound6a [187], and CompoundD4 [188]. These were designed to have low penetration in the brain, except for Compound6a, whose chronic administration caused accumulation in the brain [187]. On the other hand, clinical studies demonstrated decreased body weight and a safe administration profile for two other CB1 antagonists: AVE-1625 [174] and SLV-319 [189].…”
Section: Endocannabinoid System As a Pharmacological Target For Obesity And Food Addictionmentioning
confidence: 99%
“…MRI-1867 is a low brain penetrating CB1 inverse agonist developed for the treatment of liver fibrosis, and DIO mice treated with MRI-1867 for 28 days experienced significant reductions in body weight and food intake, and increased energy expenditure [ 68 , 170 ]. Other similar compounds include Compound 6a, BMS-725519, BMS-811064, and BMS-812204 [ 73 , 171 ]. All of these novel compounds require further investigation.…”
Section: Exploring the Direct Effects Of Cannabinoid Drugs On Bodymentioning
confidence: 99%